SISTEM INFORMASI PEMESANAN ROTI ONLINE PADA âTOKO ROTI ARNIAâ - , VERONICA DYAH AYU MAHASWI; , Faizah S.kom, M.kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The ordering data management in arnia bakery is still done using book for documenting. It cause documenting and data management process become ineffective , especially when there was many orders in huge amount at the same time. Ordering process in arnia bakery needs a system which can manage bread data, employee data, customer data, and ordering so it can increase efficiency and service quality for customer. The implementation of this bread ordering information system uses apache web server, mysql as dbms, and php programming language with codeigniter framework. The system's features such as storing facility, search and management data such as ordering data, employee, customer, location, bank, tips and trick,and bread data, system can show and print graphic from transaction report all a once too.